The Effect of ChatGPT-Assisted Writing on EFL Students’ Academic Writing Skills - Vivi Amanda; Yesi Darmayanti; Rani Zahra; Asis Ria Ningsih; Khabib Muafi; Resti Oktarisna (Universitas Pahlawan Tuanku Tambusai, 2026)
Artificial Intelligence (AI) has become increasingly significant in higher students, particularly in improving their academic writing skills. AI-powered tools such as ChatGPT offer immediate feedback, grammar correction, vocabulary enhancement, idea generation, and text organization, which can support EFL learners in the writing process. Academic writing is often considered one of the most challenging skills for EFL students due to difficulties in language accuracy, coherence, and idea development. Although many students use AI tools in writing classes, limited empirical studies have examined the direct effect of ChatGPT-assisted writing on students’ academic writing performance, especially in the Indonesian EFL context. This study aimed to investigate the effect of ChatGPT-assisted writing on EFL students’ academic writing skills. The study employed a quasi-experimental design using a pre-test and post-test control group design involving 50 higher students divided into experimental (25 students) and control groups (25 students). The experimental group received ChatGPT-assisted writing instruction, while the control group received conventional writing instruction. The findings revealed that the experimental group achieved significantly higher post-test scores than the control group (p 0.05). It can be concluded that ChatGPT-assisted writing effectively improves students’ academic writing skills.